Blood Type and Blood Pressure Correlations to Body Mass Index in Young Adults - Suwito, Bambang Edi; Kalanjati, Viskasari P; Abdurachman, Abdurachman (Folia Medica Indonesiana, 2020)
Specific ABO blood type was reported to the higher risk of having overweight and obesity. The laters had also been suggested to correlate to blood pressure. Here we studied blood type and blood pressure amongst seemingly healthy university students of IIKBW, Kediri to understand their correlations to the body mass index (BMI). The blood typing (ABO typing, Eryclone®) and blood pressure (automated digital sphygmomanometer) of 74 male and 76 female were measured in duplicate accordingly. The BMI was analysed from the student's body weight and height using a digital balance and a microtoise staturemeter, respectively. Data were analysed using SPSS 17 with p<0.05 level of significance. There were 18.7% students have A blood type, 31.3% students were B type, 44% were O and 6.0% with AB blood type. There were 30.7% students with obesity, 18% overweight, 36% normal weight and 15.3% underweight. There were 4.7% had a hypertension, 28.7% pre-hypertension, and 66.7% were normal. No significant correlations found between BMI or the blood pressure to any specific ABO blood type, except between the blood pressure and the AB blood type (r=-0.179, p=0.03). However, there was a significant correlation between BMI and blood pressure (r=0.327, p=0.000). We observed no significant associations between any specific ABO blood type with the BMI and blood pressure. However, high blood pressures amongst students with obesity were found. Males were more common to suffer from obesity and high blood pressure than females.